An Appraisal of Project Procurement Methods in the Nigerian Construction Industry - Babatunde S.O.; Opawole A.; Ujaddughe I.C. (Institute of Research and Community Outreach - Petra Christian University, 2010)
The aim of every client at the beginning of any project is to have at the end of the day a quality structure delivered on time and within budget. However, researches have shown that in most cases this aim is not met. The aim of the study that formed the basis for this paper was to identify and assess procurement methods in use in the Nigerian construction industry and identify the factors that affect the choice of the variants under the traditional and the non-conventional procurement methods. Data were collected using well-structured questionnaires administered to professionals in Lagos metropolis. Data collected were analyzed using descriptive and inferential statistics. The study reveals that the variants of traditional method of contract procurement are the most adopted in project execution in Nigeria. In making choice of procurement method, the study reveals that project completion at estimated time ranks as the highest factor considered for traditional method, while quality assurance ranks highest with non-conventional method.